(untitled) - Kotler, Philip (Upper Saddle River, NJ, 1997)
The book is organized into five parts. Part I develops the societal, managerial, and strategic underpinnings of marketing theory and practice. Part II presents concepts and tools for analyzing any market and marketing environment to discern opportunities. Part IIIexamines issues in designing marketing strategies for companies in different market positions, global positions, and stages in the product life cycle. Part IV deals with tactical marketing and how companies should handle each element of the marketing mix - products, price, place, and promotion. Finally, Part V examines the administrative side of marketing - how firms organize, evaluate, and control marketing activities
Keywords: Managerial economics,Marketing